(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
Among the primary sources for the study of the material culture in the Middle Ages, the inventaria bonorum offer a series of fundamental data to support the digital restitution of living spaces. It is not a simple list of objects but, by specific tools and an appropriate methodology, a guide through which it is possible, centuries later, to join the notary in his journey and reconstruct the original spatial layout. On these bases, the Dipartimento di studi umanistici e del patrimonio culturale (DIUM) and the Laboratorio informatico per la documentazione storico-artistica (LIDA) of the University of Udine have created a 3D restitution of the interiors of Palazzo Vanni degli Onesti in Mercatovecchio in Udine as they appeared according to the inventory drawn up by the notary Matteo Clapiceo from 4 to 17 December 1437. This made it possible to recover the lost subdivision of the rooms, the typological redistribution of furniture and furnishings, the virtual relocation of the painted wooden ceilings that have now been dismantled, and the reconstruction of the related frescoed wall decoration. That allowed to obtain an immersive experience that enables to relive customs and habits, choices of taste and colours long-forgotten, proposing a possible fifteenth-century century living dimension.